2011
DOI: 10.1590/s1415-47572011000200021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genotoxic and antigenotoxic potential of Melissa officinalis in mice

Abstract: Melissa officinalis (L.) (Lamiaceae), a plant known as the lemon balm, is native to the east Mediterranean region and west Asia. Also found in tropical countries, such as Brazil, where it is popularly known as “erva-cidreira” or “melissa”, it is widely used in aqueous- or alcoholic-extract form in the treatment of various disorders. The aim was to investigate in vivo its antigenotoxicity and antimutagenicity, as well as its genotoxic/mutagenic potential through comet and micronucleus assaying. CF-1 male mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 42 publications
1
25
0
4
Order By: Relevance
“…Recently, De CarvalhoI et al, 47 have demonstrated that M. officinalis exhibits antigenotoxic/ antimutagenic properties in mice. So in our work the effect of melissa extract as a main source of antioxidants against malathion hazard in rat testes was studied and found that the M. officinalis extract has antioxidant activity agent and could improve the biochemical and histochemical picture of rat testes against toxicity of malathion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, De CarvalhoI et al, 47 have demonstrated that M. officinalis exhibits antigenotoxic/ antimutagenic properties in mice. So in our work the effect of melissa extract as a main source of antioxidants against malathion hazard in rat testes was studied and found that the M. officinalis extract has antioxidant activity agent and could improve the biochemical and histochemical picture of rat testes against toxicity of malathion.…”
Section: Discussionmentioning
confidence: 99%
“…For cytotoxicity assays, the 50% inhibition concentration (IC 50 ), expressed as the concentration of sample that caused a 50% inhibition of enzyme activity in the cells, was applied. To calculate the IC 50 , the absorbance value of the blank was subtracted from the absorbance values of each sample, and the results were compared with the absorbance values of the solvent controls.…”
Section: Cytotoxicity Test (Mtt Test)mentioning
confidence: 99%
“…Medicinal plants are important antimutagenic and chemopreventive agents capable of preventing and/or repairing genomic changes (Malini et al, 2010;de Carvalho et al, 2011). It is estimated that 60% of anticancer drugs are derived directly or indirectly from medicinal plants ( WHO, 2011), which explains the large amount of research that aims to evaluate biological activities that demonstrate the balance and equilibrium of natural defenses through the action of antioxidants in modulating genomic repair (de Mesquita et al, 2009;Malini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%